Who Should Bear the Cost of Convenience? A Cost-effectiveness Analysis Comparing External Beam and Brachytherapy Radiotherapy Techniques for Early Stage Breast Cancer. Issue 3 (March 2017) - McGuffin, M.; Merino, T.; Keller, B.; Pignol, J.-P.
Abstract: Aims: Standard treatment for early breast cancer includes whole breast irradiation (WBI) after breast-conserving surgery. Recently, accelerated partial breast irradiation (APBI) has been proposed for well-selected patients. A cost and cost-effectiveness analysis was carried out comparing WBI with two APBI techniques. Materials and methods: An activity-based costing method was used to determine the treatment cost from a societal perspective of WBI, high dose rate brachytherapy (HDR) and permanent breast seed implants (PBSI). A Markov model comparing the three techniques was developed with downstream costs, utilities and probabilities adapted from the literature. Sensitivity analyses were carried out for a wide range of variables, including treatment costs, patient costs, utilities and probability of developing recurrences. Results: Overall, HDR was the most expensive ($14 400), followed by PBSI ($8700), with WBI proving the least expensive ($6200). The least costly method to the health care system was WBI, whereas PBSI and HDR were less costly for the patient. Under cost-effectiveness analyses, downstream costs added about $10 000 to the total societal cost of the treatment. As the outcomes are very similar between techniques, WBI dominated under cost-effectiveness analyses. Conclusions: WBI was found to be the most cost-effective radiotherapy technique for early breast cancer. However, both APBI techniques were less costly to the patient. Although innovation may increase costs for the health care system it can provide cost savings for the patient in addition to convenience. Highlights: A cost-effectiveness analysis of whole and partial breast radiotherapy techniques. Activity-based costing used to derive treatment costs from a societal perspective. High cost of brachytherapy partial breast techniques due to staffing expenditures. Whole breast irradiation is cost-effective but has highest cost to the patient. Societal perspective should be considered when adopting new technologies.